2014
DOI: 10.2528/pierb14050205
|View full text |Cite
|
Sign up to set email alerts
|

New High-Rate Uwb Scheme for Wban-Based Healthcare Systems

Abstract: Abstract-Given the emphasis on increasing wireless network usage for healthcare application, e.g., Wireless Body Area Network (WBAN), the need for high-rate physical layer has become a genuine concern from research and industrial community. The use of the Ultra-Wideband (UWB) is looking especially bright for such systems given its lower energy consumption and performances towards frequency-selective channels. However, the Multi-Band-OFDM-based UWB technique has some inherent limitations as loss in spectral eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…2. Three spots (1-3) lay on the head, six at the limbs (6,7,9,(11)(12)(13) and the rest were on the torso. The sites 4, 6, 8, 10 and 12 exist on the side of the torso, arm or leg whereas the remaining spots are situated on their frontal parts.…”
Section: Selection Of Antenna Locations and Measurement Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Three spots (1-3) lay on the head, six at the limbs (6,7,9,(11)(12)(13) and the rest were on the torso. The sites 4, 6, 8, 10 and 12 exist on the side of the torso, arm or leg whereas the remaining spots are situated on their frontal parts.…”
Section: Selection Of Antenna Locations and Measurement Implementationmentioning
confidence: 99%
“…It has been investigated both in offbody [5][6][7] and in-body cases [8]. Perhaps the majority of the published papers are related to the various aspects of on-body situations [9][10][11][12]. For instance, in [7,[13][14][15] research related to UWB onbody radio channels are reported.…”
Section: Introductionmentioning
confidence: 99%
“…The WBANs [1] [2] [3] [4] [5] are designed to support a wide range of medical applications, such as asthma, cardiovascular disease, and cancer detection. They have enormous potential to revolutionize the future of healthcare by diagnosing many deadly diseases and providing remote and real-time monitoring of patients' health status without any restrictions, which improve their quality of life and reduce their costs of hospitalization.…”
Section: Introductionmentioning
confidence: 99%